1998
DOI: 10.1002/(sici)1097-4652(199803)174:3<353::aid-jcp9>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor modulation of mitogenic responses and proteoglycan synthesis by human periodontal fibroblasts

Abstract: In order to understand the relationship between specific growth factors and matrix synthesis by periodontal cells, we have investigated the effects of platelet-derived growth factor BB (PDGF-BB), insulin-like growth factor-I (IGF-1), and growth hormone on DNA and proteoglycan synthesis by cultured human gingival and periodontal ligament fibroblasts in vitro. PDGF-BB and IGF-1, but not growth hormone, were mitogenic for both periodontal ligament fibroblasts and gingival fibroblasts, although the periodontal lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
2
16
0
2
Order By: Relevance
“…The bioactive molecules PDGF, TGF‐β 1 , and IL‐1β were chosen for this study because of their roles in both inflammation and tissue repair. PDGF‐BB induces gene expression of cell matrix‐related molecules, such as collagens and glycosaminoglycans (25, 32). In particular, PDGF‐BB upregulates the synthesis of versican, but downregulates decorin synthesis by PDLF and GF (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactive molecules PDGF, TGF‐β 1 , and IL‐1β were chosen for this study because of their roles in both inflammation and tissue repair. PDGF‐BB induces gene expression of cell matrix‐related molecules, such as collagens and glycosaminoglycans (25, 32). In particular, PDGF‐BB upregulates the synthesis of versican, but downregulates decorin synthesis by PDLF and GF (25).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were incubated for a further 8 h before the RNA was harvested. These concentrations were chosen on the basis of previous studies which have demonstrated these to be within the optimum range inducing biological responses by periodontal cells (23–25).…”
Section: Methodsmentioning
confidence: 99%
“…To examine tropoelastin mRNA expression, sample RNA was extracted from HGF and HPLF after culture for 4 wks by means of a RNeasy Mini Kit (Qiagen, Hilden, Germany), as described previously (Haase et al, 1998). Using the extracted RNA as a template, we carried out reverse-transcription reactions with a SuperScript TM First-Strand complementary DNA (cDNA) Synthesis System (Life Technologies, Grand Island, NY, USA).…”
Section: Rna Extraction and Reverse-transcription/ Polymerase Chain-rmentioning
confidence: 99%
“…Studies have suggested that periodontal ligament fibroblasts (PDLF) and gingival fibroblasts (GF) are heterogeneous (Lekic et al, 1997;Lackler et al, 2000) with extensive site-specific functional differences, including variations in responses to growth factors (Haase et al, 1998;Mumford et al, 2001). IGF-1 has been shown to regulate DNA and protein synthesis in PDLF in vitro and to enhance soft-tissue wound healing in vivo (Lynch et al, 1991;Ivanovski et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 has been shown to regulate DNA and protein synthesis in PDLF in vitro and to enhance soft-tissue wound healing in vivo (Lynch et al, 1991;Ivanovski et al, 2001). It was suggested that PDLF respond to IGF-1 more strongly than GF, and this differential response to IGF-1 could stem from the tissue specificity of these cells within the periodontium (Haase et al, 1998). However, the role of IGF-1 in preventing apoptosis in PDLF compared with GF still remains unclear.…”
Section: Introductionmentioning
confidence: 99%